Antimicrobial tolerance, biofilm formation, and molecular characterization of Salmonella isolates from poultry processing equipment - T. Obe (Elsevier, 2021)
SUMMARY: Foodborne pathogens, such as Salmonella are problematic in food processing environments, and understanding the means of persistence is critical in the development of effective control measures. This study determined the antimicrobial tolerance of Salmonella isolates from the processing environment and characterized their biofilm production and antibiotic resistance. Twenty-five Salmonella isolates were previously recovered from poultry processing equipment in commercial production facilities after sanitation. The minimum inhibitory concentration of 2 antimicrobials; chlorine and quaternary ammonium compounds that were frequently used for sanitation was determined for these isolates using the Clinical and Laboratory Standards Institute guidelines. Biofilm forming ability was assessed using the crystal violet assay and antibiotic susceptibility was also determined. These isolates were further characterized based on their genes that were responsible for biofilm formation and resistance to sanitizers and antibiotics. Minimum inhibitory concentration values between 500 and 1,000 parts per million for chlorine, or 3 to 25 parts per million for quaternary ammonium compounds were observed amongst these Salmonella isolates. These isolates possessed strong (24%), moderate (28%), and weak (48%) biofilm forming ability. All isolates were resistant to multiple antibiotics, and 64% exhibited resistance to aminoglycosides and β-lactams. Molecular characterization showed that the isolates possessed specific genes for biofilm formation, sanitizer tolerance, and antibiotic resistance. These results suggest that Salmonella isolates with low tolerance to sanitizers may remain on surfaces because of their strong biofilm forming ability.